UTILIZATION of FABRIC WASTE BY CREATING SQUARE and RECTANGULAR PATCHWORK - Authary, Nailul; Yani, Muhammad; Putri, Nurul Aisyah; Azkia, Annisa (Universitas Muhammadiyah Aceh, 2024)
Cloth waste takes 20 to 30 years to decompose. The goal that is expected to be obtained through this research is to utilize fabric waste by making patchwork in the form of square and rectangular geometric shapes. The target of this service is the students of the Banda Aceh Muhammadiyah support house. The method that will be used in this community service activity as a solution to problems in this service is to adopt action research steps which consist of four stages, namely planning, implementing observation and reflection. The results of this service are (1) Participants succeeded in learning and spreading patchwork making independently with the help of the modules and pocketbooks provided (2) Observation results showed that most of the participants were able to process cloth waste into useful products, so this activity only needed carried out in one cycle because the expected target has been achievedKeywords: Waste Fabric, Patchwork, Square, Rectangle